Cooperative game theory based load balancing in long term evolution network - Intesar, Sadia; Saha, Subarno (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.